2017
DOI: 10.1002/smll.201702567
|View full text |Cite
|
Sign up to set email alerts
|

Junction‐Free Electrospun Ag Fiber Electrodes for Flexible Organic Light‐Emitting Diodes

Abstract: Fabrication of junction-free Ag fiber electrodes for flexible organic light-emitting diodes (OLEDs) is demonstrated. The junction-free Ag fiber electrodes are fabricated by electrospun polymer fibers used as an etch mask and wet etching of Ag thin film. This process facilitates surface roughness control, which is important in transparent electrodes based on metal wires to prevent electrical instability of the OLEDs. The transmittance and resistance of Ag fiber electrodes can be independently adjusted by contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
(36 reference statements)
0
37
2
Order By: Relevance
“…Therefore, previous studies attempted to reduce surface roughness by hybridizing them with other conductive materials. 14,33,[39][40][41] However, surface planarization with thin layers may not be effective if the step heights of electrodes are considerably higher than the thickness of the subsequent layer. Herein, we aimed to develop electrodes with the smallest step height while retaining the desired high transmittance and low sheet resistance.…”
Section: Flexible Organic Solar Cell Device Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, previous studies attempted to reduce surface roughness by hybridizing them with other conductive materials. 14,33,[39][40][41] However, surface planarization with thin layers may not be effective if the step heights of electrodes are considerably higher than the thickness of the subsequent layer. Herein, we aimed to develop electrodes with the smallest step height while retaining the desired high transmittance and low sheet resistance.…”
Section: Flexible Organic Solar Cell Device Performancesmentioning
confidence: 99%
“…[29][30][31][32] Choi et al pointed out that a network height of 80 nm was extremely rough for a 140-nmthick OLED active layer. 33 Thus, there are few reports on high efficiency thin film FOSCs (> 10%) that use this type of metal networks.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a facile method that can prepare free‐standing and meter‐long polymer nanofibers (NFs) with diameters ranging from several ten nanometers to several micrometers. Electrospun NF‐templated deposition of metal NFs has been in the limelight nowadays . Metal NF meshes were typically prepared by vacuum‐depositing metal on the free‐standing polymer NF mesh templates, and subsequently transferring the obtained meshes to transparent substrates .…”
mentioning
confidence: 99%
“…[4] Recently, it has been reported that the Ag fiber electrode produced by the electrospinning process has a long length and a reduced surface roughness. [5] However, it is difficult to control the surface roughness completely, and therefore, it has limitations in the transmittance and sheet resistance.…”
Section: Objective and Backgroundmentioning
confidence: 99%